IMPORT AND MANUFACTURING GROWTH: AN EMPIRICAL ANALYSIS FROM NIGERIA - Ibrahim Yinka AGBEYINKA (International Journal of Social and Educational Innovation, 2025)
The study was undertaken to find out the impact of import growth on the development of manufacturing industry sector in Nigeria. The study adopted simple regression on the ordinary least square (OLS) regression technique. The sample size was taken from 1981 to 2015 (34 years). Consequently, secondary sources of data from the central bank of Nigeria (CBN) were used. The use of Students’ test, F-ratio and Durbin-Watson Statistic was employed in finding out the empirical variability of the regression plans and testing the presence of autocorrelation respectively. In addition, the coefficient of determination (r2) was used to test for goodness of fit. The findings of the study indicate a significant positive relationship between import growth and output in the industrial sector. A significant relationship is shown between the exchange rate and industrial sector output, though positive and contrary to a priori expectation. The lag value of the dependent variable (INDP (-1)) is shown to have a significant positive relationship with economic growth. This also meets the priori expectation. The r2 value of 57.51% shows normal goodness of fit implying that the explanatory variables adequately explained the behavior of the dependent variables. Finally, this study makes the following recommendations: Nigeria's financial authorities ought to establish rules that will make credit more accessible for financial sector investment; also Nigeria should prioritize technical education more to fortify the nation's industrial basis and boost the output of the manufacturing sector and lastly the application of industrial policies is more crucial because it directs the manufacturing sectors to import necessary resources that, when converted, would produce more and be sufficiently consistent to have a suitable influence on Nigeria's manufacturing industry development.